IMPLEMENTASI DIETETIKA KULINER PENGEMBANGAN PRODUK ES KRIM “BITHA” BERBAHAN DASAR BUAH BIT DAN HATI AYAM SEBAGAI ALTERNATIF MAKANAN SELINGAN UNTUK PENCEGAHAN REMAJA PUTRI ANEMIA - Moviana, Yenny; Hilma, Yudilla (Poltekkes Kemenkes Bandung, 2024)
Anemia is a medical condition where the number of blood cells or hemoglobin is less than normal or the level of red blood cells in the blood drops. Adolescent girls are a high risk group for anemia because they experience menstruation every month and are in a period of growth that requires more iron intake. Adolescent girls with anemia during pregnancy are at risk of giving birth to Low Birth Weight (LBW) and stunting. The onset of nutritional problems in children under two years of age is closely related to the health and nutritional preparation of a woman to become a prospective mother, in this case, adolescent girls. Pharmacological treatment with consumption of tablets (Fe) causes nausea and vomiting so that other efforts are needed such as innovation in providing food products as an alternative to help overcome the incidence of anemia in adolescent girls in meeting iron needs such as processed ice cream. In addition to having a delicious taste, ice cream also contains nutritional value that is quite good if modified with the addition of iron sources such as beetroot and chicken liver.